Patient Centered Medical Home Cooking: Community Culinary Workshops for Multidisciplinary Teams. (January 2021) - Kumra, Tina; Rajagopal, Selvi; Johnson, Kathleen; Garnepudi, Lavanya; Apfel, Ariella; Crocetti, Michael
Ideal management of chronic disease includes team based primary care, however primary care medical staff face a lack of training when addressing nutritional counseling and lifestyle prevention. Interactive culinary medicine education has shown to improve knowledge and confidence among medical students. The aim of this study was to determine whether a culinary medicine curriculum delivered to a multidisciplinary team of primary care medical staff and medical students in a community setting would improve self-reported efficacy in nutritional counseling and whether efficacy differed between participant roles. A 4-h interactive workshop that took place within the neighborhood of a primary care medical home was delivered to medical staff and students. Participants completed a voluntary questionnaire before and after the workshop that addressed participants' attitudes and confidence in providing nutritional counseling to patients. Chi-square tests were run to determine statistically significant associations between role of participant and survey question responses. Sign Rank tests were run to determine if pre-workshop responses differed significantly from post-workshop responses. Thirteen of seventeen responses related to attitudes and efficacy demonstrated significant improvement after the workshop compared with prior to the workshop. Significant differences noted between roles prior to the workshop disappear when asking the same questions after the workshop. Delivery of culinary medicine curricula to a primary care medical home team in a community setting is an innovative opportunity to collaboratively improve nutritional education and counseling in chronic disease prevention.